Trampas metodológicas y retos analíticos en etnografías a proximidad del proyecto Conga - Cavero Castillo, Martín (2025)
Based on ethnographies carried out in the same locality, one in 2016 and the other in 2019, this article analyses the different methodological traps and analytical challenges that the author confronted in order to gain the trust of the inhabitants in the vicinity of the Conga project. It first outlines the criteria that guided the choice of the study site, and then focuses on the ethnographic strategies that helped him to avoid being labelled a spy and to obtain a greater diversity of local views on the mining issue. Finally, the article analyses the analytical and methodological biases that were partially overcome from one fieldwork to the next, highlighting that this reflexive work was crucial for reconstructing his object of research. The need to describe and theorize fieldwork is argued, analyzing how its development is jointly affected by the political dynamics and the game of local moral evaluations in which the researcher’s actions are inserted.